Calf health before and after change in housing system – isolated barn vs. hutches - Nilsson, Annika (SLU/Dept. of Animal Environment and Health (until 231231), 2012)
Calf health is of importance both from a financial perspective and from an animal welfare point of view. Housing system and environment are factors affecting the calves’ health. The objective of this project was to make a review of literature on calf health and housing and to perform an observational study on calf health at Nötcenter Viken, Research Dairy Farm, Lantmännen Sweden that changed calf housing system; from a traditional indoor system (Group IN) to outdoor hutches (Group OUT). It was only the housing system that was changed; the routines and feed were the same in both systems. Frequencies of pneumonia and diarrhoea, and the use of antibiotics in the different systems were compared in this study. Pneumonia was the most common registered disease followed by diarrhoea. More than twice as many diagnoses of pneumonia were registered in Group IN (255 diagnoses) compared to Group OUT (114 diagnoses). The percentage of calves diagnosed with pneumonia in Group OUT was still high compared to earlier Swedish studies. There was a significant difference in diarrhoea between the groups (p=0.0016), although the difference was not as large as in pneumonia (30.5% of the calves in Group IN was diagnosed with diarrhoea compared to 21.3% in Group OUT). Diarrhoea as well as pneumonia was diagnosed in a higher proportion of calves compared to earlier Swedish studies. One reason for the higher percentage of registered diarrhoea could be the problem with coccidian parasites that exists on the farm, but the same proportion of treated and untreated calves was later diagnosed with diarrhoea. More antibiotics were used for treatments in Group IN than in Group OUT; 63% and 37% respectively of the total use of antibiotics during the study period. Most of the antibiotics were used for treatment of pneumonia. Age at diagnosed diarrhoea was usually between 5 and 18 days of age with the highest number of calves at 9 days of age in Group IN and 11 days in Group OUT. Age at diagnosed pneumonia was more evenly spread in ages and did not have a peak at a specific age, but both groups seemed to follow a similar trend.